Screening for depression with a brief questionnaire in a primary care setting : validation of the two questions with help question. - Mohd Sidik, Sherina; Arroll, Bruce; Goodyear-Smith, Felicity; Md. Zain, Azhar (Baywood Publishing, 2011)
Objective: To determine the diagnostic accuracy of the two questions with help question (TQWHQ) in the Malay language. The two questions are case-finding questions on depression, and a question on whether help is needed was added to increase the specificity of the two questions. Method: This cross sectional validation study was conducted in a government funded primary care clinic in Malaysia. The participants included 146 consecutive women patients receiving no psychotropic drugs and who were Malay speakers. The main outcome measures were sensitivity, specificity, and likelihood ratios of the two questions, the help question, and combination of the two questions and help question. Results: The two questions showed a sensitivity of 99% (95% confidence interval 88% to 99.9%) and a specificity of 70% (62% to 78%), respectively. The likelihood ratio for a positive test was 3.3 (2.5 to 4.5) and the likelihood ratio for a negative test was 0.01 (0.00 to 0.57). The addition of the help question to the two questions increased the specificity to 95% (89% to 98%). Conclusion: The two questions on depression detected most cases of depression in this study. The questions have the advantage of brevity. The addition of the help question increased the specificity of the two questions. Based on these findings, the TQWHQ can be strongly recommended for detection of depression in government primary care clinics in Malaysia. Translation did not appear to affect the validity of the TQWHQ.